Comparative Analysis of Murabahah Financing Agreement with Musyarakah Mutanaqisah Financing Agreement in Indonesia's Sharia Banking System - Maulan, Anas; Harahap, Burhanudin; Sasmini (NAJAHA, 2023)
Indonesia is one of the largest Islamic countries in the world. In 2021, Indonesia has officially formed Bank Syariah Indonesia combined with 3 private Islamic banks, namely Bank BRI Syariah, Bank Mandiri Syariah and BNI Syariah. The purpose of Bank Syariah Indonesia is to facilitate sharia-based services that avoid customers from transactions containing elements of usury, gharar, maisir, haram and Zalim which are commonly applied in conventional banking in general in the form of interest. Islamic banking in Indonesia takes advantage not from usury but from financing or buying and selling goods carried out by banks with customers according to customer wishes and needs. One of the financing that is usually in demand by customers is the murabahah financing contract and the musyarakah mutanaqisah financing contract. These two contracts are the same as taking advantage of buying and selling goods but murabahah is more dominant in financing without a down payment and goods that have been determined from the beginning of the contract while muyarakah mutanaqisah is more dominant in financing the needs desired by customers in the form of cash instead of goods.